Project based learning (pjbl) terhadap kompetensi akademik mahasiswa keperawatan: review sistematis - Dwi Pratiwi, Gilang (STIKES Bethesda Yakkum, 2024)
Nursing competence is an important thing that must be achieved by nursing graduates, and it is essential to apply various learning methods. Purpose this study aims to review the effectiveness of Project-based Learning in improving academic competence in nursing students. Method the systematic review was applied in this study using PRISMA analysis. Result from the search stage according to the PRISMA method, there were 5 articles included in this study. The entire article shows positive results between the implementation of PjBL on the competence of nursing students. Of the 5 articles, 2 articles used a quasi-experimental research design with pre and post-tests, 2 articles with observational descriptions, and 1 article was qualitative article. Discussion PjBL can increase the competence of nursing students because it is constructive and involves students actively starting from planning, processing, preparing the final product, and reporting or presentation of results. With the complexity of the learning process, student competence becomes sharpened and increases. Conclusion the project-based learning model is effective in increasing the competence of nursing students.